Coloniality, decolonization and interculturality. Notes from Intercultural Philosophy (Polis (Santiago), 2018)
This short essay reframes the debate on the subject stated in the title from the perspective of an intercultural philosophy critical and liberationist, seeking to clarify the concepts involved and distinguish between postures more or less "naive" or "celebratory" of the interculturality/decolonization, on one hand, and "critical" and "emancipatory" postures on the other hand. We are at an historic point in which the discourse of "interculturality" and "decolonization" undergoes a process of wear and cooptation by the hegemonic monocultural and globalizing model in the sense of a Western cultural imperialism and of a postmodernity in consumerism key.
Keywords: colonialism; decolonization; multiculturalism; social justice; gender equity